Teaching and learning activities - Norazwina, Zainol (Kolej Kejuruteraan, 2020)
College of Engineering provides enormous possibilities and choice to students who want to study Engineering with different fields of undergraduate, Masters by Course and Research in all fields of speciality. Equipped with excellent laboratory setups, the college is ready to provide the best education and opportunities to students according to their interests and talents. UMP open registration system allows our students to choose their courses according to their plan. Besides the basic engineering courses, students are trained in soft skills, languages and arts which help students to become all rounded future leaders in their respective community. We have strategic collaboration with other peer institutions and industries to help achieving excellence in teaching and learning activities